Energizing beverages and its adverse effects in the university population - Hernández Romero, Deisy
Energy drinks are a group of products that enjoy a high popularity for their stimulating properties and their harmless characteristics that are attributed to it. The general objective is to expose about energy drinks and their adverse effects on the university population, analyzing its composition, its consequences on health and consumption. As for the methodology, it is a documentary research, through a bibliographic review, for which, approximately 80 articles were consulted, the inclusion parameters being related to the subject matter of the study, taking into account that they were starting from 2000 to 2018, published in different databases, it was also consulted in books and magazines in different libraries of universities in the city of Bogotá. Regarding the results, when comparing the data obtained from the selected researches and published by other authors, it was observed that the percentage of consumption of energy drinks in the university population, seen by groups of countries, ranges between 35 and 70%. As a discussion, it was found that the results found evidence that the use of energy drinks in the university population worldwide is too high, with the consumption of these beverages becoming more frequent. There are data that the use of energizers by university students, is associated with the mixture with alcohol, in a high percentage (88%), used to neutralize the effect that this produces. It is concluded that the prevalence in the university population is high, when the consumption of energy drinks is frequent, excessive or combined with other beverages such as alcohol, generating a potential risk in health, according to the analysis made to the selected studies, in which, their greatest contribution is to show the latent danger that energy drinks have when they are mixed with alcohol; emphasize that it is necessary to continue research to prevent the consequences of consuming these beverages and finally, propose to create an educational program where they report the consequences of these beverages, in order to restrict their consumption in populations at risk.